2018
DOI: 10.18203/2394-6040.ijcmph20181232
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practices of secondary school teachers regarding school health services in children

Abstract: INTRODUCTIONGood health and good education provide individuals to lead productive and satisfying lives. Physical activity, quality education with good health and nutrition are responsible for development of child's ability to attain her or his full potential. Children and youth are recognized as prime population. Academic success, optimal health and well-being of its children and youth predict national development. Schools are important settings for comprehensive health promotion. Schools exert maximum influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 4 publications
3
7
2
Order By: Relevance
“…We observed that 22% of participants had training regarding components of school health, which was more than (7.6%) that reported by Chavan et al 11 A lower level of training has clearly been reflecting in knowledge status of schoolteachers regarding various aspect of school health services. Regarding the adequate ratio of students per class in schools, only 11 (22%) participants answered correctly, five (10%) participants answered correctly for the number of students per latrine/toilet ratio, 14 (28%) participants answered correctly for adequate lighting of a room in the school.…”
Section: Discussioncontrasting
confidence: 60%
“…We observed that 22% of participants had training regarding components of school health, which was more than (7.6%) that reported by Chavan et al 11 A lower level of training has clearly been reflecting in knowledge status of schoolteachers regarding various aspect of school health services. Regarding the adequate ratio of students per class in schools, only 11 (22%) participants answered correctly, five (10%) participants answered correctly for the number of students per latrine/toilet ratio, 14 (28%) participants answered correctly for adequate lighting of a room in the school.…”
Section: Discussioncontrasting
confidence: 60%
“…Findings from the study also revealed that attitude towards school health services among respondents was positive. Supporting this finding is a study in India where it was reported that 90% of the respondents had favorable attitude to school health services [10]. No doubt this positive attitude in this present study must have resulted from good knowledge on school health services which has led to a concomitant development of positive attitude towards it.…”
Section: Discussionsupporting
confidence: 77%
“…Nutritional interventions may alter students' eating behaviors, especially because they are growing (8). Teachers' knowledge of good eating habits may transmit a favorable attitude toward healthy foods (9). Teachers' knowledge of healthy eating might improve their students' quality of healthy eating.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, teachers must undertake interventions to promote healthy eating (10). There is a growing body of evidence to suggest that unhealthy dietary choices resulting from a lack of knowledge and misconceptions about healthy foods cause some health problems such as obesity (9). A study showed that a teacher's nutrition education gained greater acceptance among children than information transmitted by an outside nutrition expert (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation